SISTEM PAKAR DIAGNOSA STUNTING BALITA MENGGUNAKAN NAIVE BAYES - Andayani, Mastra; Putrawansyah, Ferry; Syahri, Riduan (Jusikom : Jurnal Sistem Komputer Musirawas, 2025)
This study aims to develop an expert system to diagnose stunting in toddlers using the naive bayes method. Stunting is a serious health problem that is often ignored due to lack of public awareness and limited access to health services. This expert system is designed to diagnose stunting based on symptoms inputted by the user without having to consult directly with medical personnel. The naive bayes method is used to handle uncertainty in the data and provide a level of certainty in the diagnosis. Research data were obtained through observation, interviews with medical personnel at the Health Office, and literature studies. This system was developed using the PHP programming language and MySQL database, and tested using the blackbox testing technique. This system is expected to increase awareness and early detection of stunting, while supporting the Health Office in its efforts to reduce the prevalence of stunting.